Research design of stakeholder networks in a tourist destination - Pavlović, Damir (Oeconomica Jadertina, 2024)
The aim of this work is to make a critical analysis of research design in tourism with an emphasis on stakeholders in the destination network, which should result in finding the most optimal research and methodological model for the purpose of scientific and practical application in adaptable and efficient destination management. The paper considers a wide range/map of research design and approach in all phases of the research process: data collection and processing, and interpretation of the obtained results. Recommendations for finding an adequate methodological approach to research in tourism and tourist destinations were obtained by testing, that is, by projecting the specificity of the research process in tourism onto the general research matrix/paradigm represented by the successive gradation of research steps: context, paradigm, epistemology, general methodological orientation and applied concrete methods. The so-called method of chain referral proved to be the most effective in collecting data on the topological structure of the destination network of stakeholders. A hybrid explanatory sequential design in a combination of quantitative and qualitative methodological approach seems to be the most optimal and can be the most useful in researching the relationship between stakeholders in the management of a tourist destination. In previous research in the conceptual field of destination stakeholder networks, the proposed research model is not as specified and focused as in the case of this paper. management. However, there are also certain limitations of this work, which primarily refer to the need for multiple testing of the proposed research model on concrete case studies. Following the highlighted limitations in future research, it is recommended to test the proposed methodological approach and concept on case studies of two qualitatively different destination networks of stakeholders (e.g. coastal and continental) in Croatia to confirm its validity.
Keywords: Keywords: stakeholders, destination network, research design, methodological approach. explanatory sequential design